Artificial maintenance of the relative ocular tissue pressure during eye surgery. Issue 8 (August 1990) - Maggi, C.; Maggi, R.
Abstract : We describe an operating table in which the whole patient, apart from the eye undergoing surgery, is enclosed in a caisson within which the barometric pressure can be lowered at any time during surgery. This increases the effect of atmospheric pressure on the eye, enabling 'open sky' surgery to be carried out on patients of any age.